MEASUREMENT OF AGILITY LEVEL IN HOSPITALS SUPPLY CHAINS - Martins, A.; Helgheim, B. (10th International Symposium on Logistics, 2005)
Agility and agile supply chains are increasingly mentioned in literature. Focus of research has been manufacturing contexts and not much research has been performed in terms of services. Taking into consideration that the service sector represents around 70% of GDP in many advanced economies, a major gap in research has to be closed. This paper aims at analysing the level of agility in services supply chains. Using the Sand Box Model, a questionnaire was developed and applied to analyse the level of agility in the supply chains of Portuguese hospitals with private administration. It was not found any consistent relevance of location or dimension in the degree of agility. Limitations of this research are identified as well as topics for further research.